Genetic Variability of Reproductive Organs of Atlas Pistachio in Tiaret Region, Algeria - Mehdeb-Hireche, Djamila; Azzaoui, Mohamed El Saleh; Chahbar, Safia; Benhassaini, Hachemi (International Journal of Bio-resource and Stress Management, 2021)
Pistacia atlantica Desf., endemic to northern Africa belonging to the family Anacardiceae, is a dioecious species of great ecological and socio-economic importance that exhibits considerable variation between individuals but some cases of monoecis have been discovered within the same family such as Pistacia atlantica Desf., Pistacia therebinthus and Pistacia chinensis. The study was conducted to find for the existence of genetic variability of the Betoum from mid-February to mid-March. The study is made on the morphological parameters of reproductive organs of four sites in the Tiaret region in Algeria. The results showed that this species has a high polymorphism of the morphological, qualitative and quantitative parameters of the reproductive organs. This variation is found in the male and female individuals of the selected stands. Variations in these reproductive organs can in no way be influenced by climatic changes such as leaves and roots and their physiological, biochemical and anatomical parameters. This allowed us to discover the first case of the monoicy in the Rechaiga forest. It is necessary to carry out thorough studies to know all the effects and benefits that this species can bring in our daily life in all the social, ecological and economic medicinal fields with the aim of a better appreciation of the patrimony than presents this species, the maintenance of genetic diversity, its conservation and the prospects for its development.